Effect of sildenafil on skeletal and cardiac muscle in Becker muscular dystrophy. Issue 4 (15th July 2014) - Witting, Nanna; Kruuse, Christina; Nyhuus, Bo; Prahm, Kira P.; Citirak, Gulsenay; Lundgaard, Stine J.; von Huth, Sebastian; Vejlstrup, Niels; Lindberg, Ulrich; Krag, Thomas O.; Vissing, John
<x xml:space="preserve">Abstract</x> Objective Patients with Becker muscular dystrophy (BMD) and Duchenne muscular dystrophy lack neuronal nitric oxide synthase (nNOS). nNOS mediates physiological sympatholysis, thus ensuring adequate blood supply to working muscle. In mice lacking dystrophin, restoration of nNOS effects by a phosphodiesterase 5 (PDE5) inhibitor (sildenafil) improves skeletal and cardiac muscle performance. Sildenafil also improves blood flow in patients with BMD. We therefore hypothesized that sildenafil would improve blood flow, maximal work capacity, and heart function in patients with BMD. Methods A randomized, double‐blind, placebo‐controlled crossover design with two 4‐week periods of treatment, separated by 2‐week washout was used. We assessed brachial artery blood flow during maximal handgrip exercise, 6‐minute walk test, maximal oxidative capacity, and life quality; cardiac function was evaluated by magnetic resonance imaging (MRI) at rest and during maximal handgrip exercise. Muscle nNOS and PDE5 were tested with Western blotting in 5 patients. Results Sixteen patients completed all skeletal muscle evaluations, and 13 completed the cardiac MRI investigations. Sildenafil had no effect on any of the outcome parameters. No serious adverse effects were recorded. PDE5 and nNOS were deficient in 5 of 5 biopsies. Interpretation Despite positive evidence from animal models of dystrophinopathy and physiological findings in patients with BMD, this double‐blind, placebo‐controlled clinical study showed no effect of sildenafil on blood flow, maximal work capacity, and heart function in adults with BMD. This discrepancy may be explained by a significant downregulation of PDE5 in muscle. Ann Neurol 2014;76:550–557